Modeling interdependencies in multi-sectoral critical infrastructure systems: Evolving the DMCI approach. (November 2020) - Galbusera, Luca; Trucco, Paolo; Giannopoulos, Georgios
Highlights: Interdependencies are studied at service level. The approach is generic and sector agnostic. Service demand levels are considered to identify infrastructure inoperability. Demand shift to infrastructures providing similar services is considered. DMCI can be federated with sector specific models. Abstract: The adequate functioning of critical infrastructures is crucial for sustaining the development of today's societies and economies. It is a priority, therefore, to foster our understanding of such systems and ability to assess interdependencies, vulnerabilities, and resilience. Starting from the DMCI (Dynamic functional Modelling of vulnerability and interoperability of Critical Infrastructure systems) framework proposed in [1], in this paper we present an evolved formalism (DMCI-e). This introduces novel modeling features and enhances applicability while keeping the original focus on a dynamic and network-centric characterization of disservice. A key objective is to respond to the need, expressed by policy-makers and critical infrastructure regulators, for sector-agnostic and multi-granular infrastructure models for the estimation of service supply capabilities and response during and after disruptive events.